THE ROLE OF EMPLOYEE TRAINING AND ACCESS TO INFORMATION ON PRODUCTIVITY FOR SAFARICOM RETAIL OUTLETS IN UASIN GISHU COUNTY, KENYA - Edung, Jackline Ochola; Okello, Stephene (Archives of Business Research, 2019)
<span style="line-height: 115%; font-family: 'Footlight MT Light',serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: SW; mso-fareast-language: SW; mso-bidi-language: AR-SA;" lang="SW">This study sought to establish the role of training of employees and access to information on productivity in Safaricom PLC retail shops. Service systems industry play a pivotal role in modern industries’ productivity today. One such system is the telecommunication industry service systems, which offer varied services that are essential to individuals as well as corporates. The productivity of Safaricom PLC retail shops is determined by business service system success which ensures increased sales and therefore higher profits. To achieve success managers adopt strategies such as employee training and access to the right information among others. Despite these measures in telecommunications industry, it has proved in some cases not to be successful in achieving high productivity. The company can take their retail traders for training but still the output remains dismal.It has been confirmed that some agents have access to the right information but still cannot deliver services to high-level satisfaction of customers. The study had a target population of 444 respondents which were from Safaricom PLC outlet in Uasin Gishu County Kenya. This study adopted a survey design based on a sample drawn from across Safaricom PLC Retail Shops in Uasin Gishu County. Further, The study used Krejcie and Morgan table (1970) to calculate the sample size of 205 which represented employees of Safaricom PLC in the study area. Questionnaires and interview schedules were then used to collect the data, which were analyzed using statistical package for social science (SPSS). The study established that training and access to information across the retail stores increased productivity levels by 70% as per the Net Promoter Score (NPS) assessments. The study recommends consistency in employee training since necessary skillsets promote personalized experience and productivity. <span style="line-height: 115%; font-family: 'Footlight MT Light',serif; font-size: 12pt; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: SW; mso-fareast-language: SW; mso-bidi-language: AR-SA;" lang="SW">